Anotaciones sobre el sistema hegeliano: Idea, desenvolvimiento y libertad. (2021)
The text that is presented tries to approach to the System of Hegel from a particular consideration: the unfolding of the Idea - fundamental term of his philosophy- since some interpretations have presented the System of Hegel like a “rigid scheme” in which the unfolding of the Idea is finished. On the contrary, I try to make one first approach to the System showing how the route of the Idea is not finished, but on the contrary, it must be understood like a circle of circles (movement of overcoming in spiral). The text has as main theme the problem of the Freedom and like so the location of this one the System.